Air drying device for duck egg processing - ZHA ANCHUN; LIANG YONG; ZHU WANJING; YIN HENGBING; ZHANG WANLIN; CHEN JING (2024)
The utility model discloses an air drying device for duck egg processing, which comprises a placing table and fans, the fans are fixedly arranged on the two sides of the placing table, a plurality of through holes are formed in the two sides of the placing table, and a plurality of placing grooves are formed in the placing table. Duck eggs are placed in a placing groove in a placing table, at the moment, the duck eggs abut against a protruding block, a motor is started, the motor controls a driving rod to rotate, the driving rod controls a second rotating block to slide in a swing rod, the swing rod rotates relative to the placing table, a first rotating block slides relative to the swing rod, and a reciprocating plate fixedly connected with the first rotating block slides relative to the placing table; when the reciprocating plate slides, the convex blocks on the reciprocating plate slide in the placing grooves, so that the duck eggs in the placing grooves roll, and all parts of duck egg shells can be quickl